PELAKSANAAN SUPERVISI KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU ALQURAN HADITS MTS JAUHARUL FALAH SUNGAI TERAP MUARO JAMBI - Fathulloh (UNISAN JURNAL, 2024)
The implementation of the madrasa head’s supervision of Al-Quran Hadith teachers at MTs Jauharul Falah Sungai Terap Muaro Jambi is the main topic of this research. In the context of Islamic religious education, the quality of Al-Quran Hadith teachers has an important role in shaping the character and morality of the young generation of Indonesian Muslims. However, the implementation of supervision often still faces obstacles that can affect teacher performance. Therefore, this research aims to identify the factors that influence the implementation of supervision and its impact on the performance of Al-Quran Hadith teachers at MTs Jauharul Falah Sungai Terap Muaro Jambi. The research method used is a qualitative approach with descriptive research type. Data was collected through observation, interviews and documentation studies. The results of the research show that the implementation of the madrasa head’s supervision of Al-Quran Hadith teachers at MTs Jauharul Falah Sungai Terap Muaro Jambi still faces several obstacles. Factors that influence the implementation of supervision include the madrasa head’s lack of understanding of the concept of supervision, the madrasa head’s lack of skills in carrying out supervision, lack of management support, and internal teacher factors such as motivation, teaching ability, and readiness. Nevertheless, the implementation of supervision has a significant positive impact on the performance of Al-Quran Hadith teachers. These impacts include improving the quality of learning, increasing motivation, improving teaching skills, and increasing the achievement of educational goals. With effective supervision, it is hoped that the performance of Al-Quran Hadith teachers at MTs Jauharul Falah Sungai Terap Muaro Jambi can continue to improve so that the objectives of Islamic religious education at the madrasah can be achieved well. In order to increase the effectiveness of supervision, it is recommended that madrasa heads increase their understanding and skills in carrying out supervision, as well as obtain greater support from management. Apart from that, teachers also need to increase motivation, teaching ability, and readiness to receive input from supervision. Thus, supervision can be an effective strategy in improving the quality of Islamic religious education at MTs Jauharul Falah Sungai Terap Muaro Jambi. Keywords: